Stereotactic body radiotherapy in the management of hepatocellular carcinoma: An Australian multi‐institutional patterns of practice review. Issue 3 (22nd April 2021) - Liu, Howard Yu‐hao; Lee, Yoo‐young Dominique; Sridharan, Swetha; Choong, Ee Siang; Le, Hien; Wang, Wei; Khor, Richard; Chu, Julie; Oar, Andrew; Mott, Rebekah; Smart, Joanne; Jenkins, Trish; et al.
Abstract: Introduction: Stereotactic body radiotherapy (SBRT) is an emerging, therapeutic option in the management of hepatocellular carcinoma (HCC). A multicentre Liver Ablative Stereotactic Radiation (LASR) database was established to provide a collaborative platform for Australian institutions to define the practice of liver SBRT for HCC. This study explores the patterns of SBRT practice amongst Australian institutions. Methods: This was a multi‐institutional retrospective study of patients treated with SBRT for HCC at 10 institutions between January 2013 and December 2019. Patients' demographics, disease characteristics and SBRT details were evaluated. Results: Three hundred and seventeen patients were evaluated with a median age of 67 years (range, 32–90). Liver cirrhosis was present in 88.6%, baseline Child‐Pugh score was A5/6 in 85.1% and B7/8 in 13.2%. Median size of HCC treated was 30 mm (range, 10–280). 63.1% had early‐stage disease (Barcelona clinic liver cancer (BCLC) stage 0/A) and 36% had intermediate/advanced‐stage disease (BCLC B/C). In 2013/2014, six courses of SBRT were delivered, increasing to 108 in 2019. SBRT was prescribed in five fractions for 71.3% of the cohort. The most common dose fractionation schedule was 40 Gy in five fractions (24.3%). Median biologically effective dose (BED10 ) delivered was 85.5 Gy for early‐stage and 60 Gy for intermediate/advanced disease, respectively. The most common prescription range was 100–120 Gy BED10 (32.8%). Conclusion: SBRT utilisation for HCC is increasing in Australia. There was wide variation in size of tumours and disease stages treated, and prescription patterns. Uniform reporting of clinical and dosimetric details are important in refining the role of liver SBRT.